RETRACTED: Digital design trends of train and shunting operations at railway stations - Suyunbayev Shinpolat; Khudayberganov Sakijan; Jumayev Sherzod; Bashirova Alfiya (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001